2020
DOI: 10.3390/biomedicines8100423
|View full text |Cite
|
Sign up to set email alerts
|

S-Methylcysteine (SMC) Ameliorates Intestinal, Hepatic, and Splenic Damage Induced by Cryptosporidium parvum Infection Via Targeting Inflammatory Modulators and Oxidative Stress in Swiss Albino Mice

Abstract: Cryptosporidiosis has been proposed to be one of the major causes of diarrhoeal disease in humans worldwide that possesses zoonotic concern. Thereby, this study investigated the potential effects of s-Methylcysteine (SMC) on the parasite in vivo followed by the measurement of cytokines, oxidative stress parameters, and an investigation of the major histopathological changes. Sixty male Swiss albino mice weighing 20–25 g were allocated equally into five groups and orally administered saline only (control), SMC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 78 publications
3
11
0
Order By: Relevance
“…Serum levels of liver enzymes (AST and ALT) and serum urea showed high significant increase in the infected control group compared to the normal control one. This is consistent with earlier studies that found an increase in liver enzymes during Cryptosporium infection [ 1 , 18 , 44 ]. This can be explained due to hepatocytes damages that induced by the parasite as elevated AST indicates mitochondrial damage and elevated ALT signaling cell membrane injury [ 45 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Serum levels of liver enzymes (AST and ALT) and serum urea showed high significant increase in the infected control group compared to the normal control one. This is consistent with earlier studies that found an increase in liver enzymes during Cryptosporium infection [ 1 , 18 , 44 ]. This can be explained due to hepatocytes damages that induced by the parasite as elevated AST indicates mitochondrial damage and elevated ALT signaling cell membrane injury [ 45 ].…”
Section: Discussionsupporting
confidence: 94%
“…The same results observed when treated cryptosporidiosis Swiss albino mice with S-Methylcysteine at doses of 25 and 50 mg/kg body weight. significantly led to correcting the levels of GSH and as SOD activity toward the control level [ 18 ]. The antioxidant potential of crude extract of Solanum nigrum leaves and its active constituents as treatment against restraint stress in rat’s liver was evaluated, and it was found that tested extract was confirmed by the deterioration of stress change in ALT and AST marker enzymes toward their normal values [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, using plant-based compounds to control the poultry coccidiosis would help avoid the chemical therapy's resistance. Garlic extract compounds, such as SMC, were reported previously to have an antiprotozoal effect against the Cryptosporidium parvum infection in mice ( 44 ). In this study, the anticoccidial effect of SMC was investigated in poultry for the first time and compared to diclazuril's anticoccidial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a natural antioxidant and herbal medications are being evaluated. Recently, increased attention has been paid to the use of herbal medications as remedies for various parasitic diseases (7)(8)(9)(10). Spirulina platensis (SP) is a natural spiral-shaped, multicellular photosynthetic, bluegreen microalga (Cyanobacterium).…”
Section: Introductionmentioning
confidence: 99%